Fashionable Democracy: Banalitas Iklan Politik di Ruang Publik - ALI MINANTO (Komunikator, 2014)
Convergence of political and economic liberalization that swept the ‘new democracies’ countries makes political events as an industry. Electoral democracy which makes direct elections as the way has led democracy subject to the codes of consumerism. Political advertising, as a form of political communication was packaged as commodities that rely on images. Political rite and democracy agenda aligned uniformly refer to American style (Americanized) that uses imagery. In a way, democracy has lost its orientation towards the ideal of creating equality and freedom. Democracy which is trapped as a procedural mechanical activity without value and only a trend is devoid of the ideals of change and political maturation. Keywords : political advertising, fashionable democracy, banality